2017
DOI: 10.1159/000464115
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM4B Predicts Axillary Lymph Node Metastasis in Breast Cancer and Promotes Breast Cancer Cell Aggressiveness in Vitro

Abstract: Purpose: Lysosome-associated protein transmembrane-4 beta (LAPTM4B) is associated with the prognosis of several human malignancies. In this study, the role of LAPTM4B in the metastatic potential of breast cancer (BC) and its underlying molecular mechanisms were investigated. Methods: The relationship between LAPTM4B expression and axillary lymph node metastasis was determined in 291 BC specimens by immunohistochemistry. The expression of LAPTM4B in paired BC cells was overexpressed and inhibited to analyse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…In this research, transwell assays showed that the inhibition of migration and invasion induced by AP4 knockdown could be abrogated by restoring LAPTM4B expression, which was consistent with the expression of epithelial–mesenchymal transition (EMT)‐related proteins on immunoblot analysis. Although a series of clinical experiments have shown that various kinds of carcinomas with LAPTM4B‐35 overexpression present more invasive characteristics, the mechanism of the effect of LAPTM4B on migration and invasion is still unclear (Xiao et al ., ). Previous researches suggested that the possible mechanism of the effect of LAPTM4B on migration and invasion was the interaction between LAPTM4B and SH3 domain‐containing proteins that are involved in many signalling pathways (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In this research, transwell assays showed that the inhibition of migration and invasion induced by AP4 knockdown could be abrogated by restoring LAPTM4B expression, which was consistent with the expression of epithelial–mesenchymal transition (EMT)‐related proteins on immunoblot analysis. Although a series of clinical experiments have shown that various kinds of carcinomas with LAPTM4B‐35 overexpression present more invasive characteristics, the mechanism of the effect of LAPTM4B on migration and invasion is still unclear (Xiao et al ., ). Previous researches suggested that the possible mechanism of the effect of LAPTM4B on migration and invasion was the interaction between LAPTM4B and SH3 domain‐containing proteins that are involved in many signalling pathways (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…LAPTM4B (the lysosome-associated protein transmembrane-4b gene) is considered as an oncogene, and its overexpression has been proven to promote the proliferation of various tumor cells, boost invasion and metastasis, resist apoptosis, initiate autophagy, and assist drug resistance. [35][36][37][38] Overexpression of LAPTM4B in breast cancer cells results in resistance to anthracycline, and its knockdown can sensitize the drug response. 39 NGFRAP1 (nerve growth factor receptor-associated protein 1) is an apoptosisrelated gene, and its expression is downregulated in some solid organ malignancies and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these results came from studies conducted in Hela cells, and the role of LAPTM4b for mTORC1 activity was confirmed in MDA-MB-231 (breast) or HEPG2 (liver) cancer cells [17]. In addition, LAPTM4b is overexpressed in breast cancers compared with normal breast tissue, and it is more highly expressed in more advanced cancers, indicating that it is associated with breast cancer progression [19,20]. …”
Section: Lat1 Promotes Mtorc1 Activitymentioning
confidence: 99%